Erratum to: Partial versus Productive Immunoglobulin Heavy Locus Rearrangements in Chronic Lymphocytic Leukemia: Implications for B-Cell Receptor Stereotypy - Eugenia Tsakou; Andreas Agathagelidis; Myriam Boudjoghra; Thorsten Raff; Antonis Dagklis; Maria Chatzouli; Tatjana Smilevska; George Bourikas; Helene Merle-Beral; Eleni Manioudaki-Kavallieratou; Achilles Anagnostopoulos; Monika Brüggemann; et al. (BMC, 2013)
Eugenia Tsakou, Andreas Agathagelidis, Myriam Boudjoghra, Thorsten Raff, Antonis Dagklis, Maria Chatzouli, Tatjana Smilevska, George Bourikas, Helene Merle-Beral, Eleni Manioudaki-Kavallieratou, Achilles Anagnostopoulos, Monika Bru.ggemann, Frederic Davi, Kostas Stamatopoulos, and Chrysoula Belessi. (2012) Partial versus Productive Immunoglobulin Heavy Locus Rearrangements in Chronic Lymphocytic Leukemia: Implications for B-Cell Receptor Stereotypy. Mol. Med. 2012 Feb 10;18:138-45.